Reusable Macroporous Oil Sorbent Films from Plastic Wastes - Junaid Saleem (14670322) (2022)
Plastic waste comprises 15% of the total municipal solid waste and can be a rich source for producing value-added materials. Among them, polyethylene (PE) and polypropylene (PP) account for 60% of the total plastic waste, mainly due to their low-end and one-time-use applications. Herein, we report reusable oil sorbent films made by upcycling waste PE and PP. The as-prepared oil sorbent had an uptake capacity of 55 g/g. SEM analysis revealed a macroporous structure with a pore size range of 1–10 µm, which facilitates oil sorption. Similarly, the contact angle values reflected the oleophilic nature of the sorbent. Moreover, thermal properties and crystallinity were examined using DSC, while mechanical properties were calculated using tensile testing. Lastly, 95% of the sorbed oil could be easily recovered by squeezing mechanically or manually. Other Information Published in: Polymers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/polym14224867